Efeito do extrato de Melia azedarach L. sobre o sistema colinérgico em ratos intoxicados com metilcarbamato - Ferreira, Fabiana Sari (2017)
Carbamates are essential products for pesticide formulation, mainly used in agriculture for the elimination of insects. Although the production and trade of carbamates are for purpose insects elimination, it is common used to suicide attempts in our environment, in addition to accidental poisonings involving rural workers and children. The toxicological property is inhibit the acetylcholinesterase and buthyrylcholinesterase enzymes which leads a severe poisoning related to cholinergic crisis. The enzymes activity get back to normal only spontaneously, so the study of new substances that can intervene directly on the active site of these enzymes when it is inhibited and reverse this toxic action is necessity for the health. Researchs with Melia azedarach L. (Meliaceae) has been made searching for new strategies for treatment of enzime inhibity by methyl carbamate poisoning. Different concentrations of Melia azedarach L. buffered extract were tested in vitro and in vivo for acetylcholinesterase activity inhibited by methylcarbamate. The results showed that the extract of Melia azedarach L. has a potential reversion effect on the enzyme inhibited by methyl carbamate, becoming an alternative to treatment of carbamate intoxication